International Dialogue: Our Experience in a Family Therapy Program - Mcdowell, Teresa; Fang, Shi-Ruei; Griggs, Julie; Speirs, Karl; Perumbilly, Sebastian; Kublay, Aliye Ebru (Journal of Systemic Therapies, 2006)
In this paper, we report our experiences as part of an international dialogue group within a U.S. family therapy training program. We describe the dialogue group and share the outcomes of our work together, including our understandings of how global relations, social positions, and personal/cultural characteristics influence our interactions within local contexts. We discuss how participation increased our international awareness and competence, offering two illustrations of how the group helped participants consider family therapy practice and research from a global perspective. Finally, we share the subjective experiences of student group members from the Southern United States, India, Turkey, and South Africa as testimony to the value of cross-national dialogue and to making space for affirming the unique journeys of international learners.
Keywords: dept.mft; peer-reviewed

Viewing the Asian American Experience Through a Culturally Centered Research Lens: Do Scholarship in Family Science and Related Disciplines Fall Short? - Fang, Shi-Ruei Sherry; McDowell, Teresa; Goldfarb, Katia P.; MacDonald, Angella; Perumbilly, Seb; Gonzalez-Kruger, Gloria E. (Marriage & Family Review, 2008)
To better understand and serve Asian-Americans, it is imperative for the family science related fields to take a leadership role in providing in-depth insight into Asian-American families. In this article we report a descriptive analysis of articles published in prominent family-based journals over a 14-year period (1992–2006) relative to their attention to Asian-American families. This study examines the types of research conducted and the knowledge that has been generated about Asian-American families. It also provides a framework for considering future culturally centered research with this population.
_eprint: https://doi.org/10.1080/01494920802185058
Keywords: Asian-Americans; culturally sensitive research approaches; dept.mft; family science; peer-reviewed

Working with Asian Indian American Families: A Delphi Study - Khanna, Anchal; Mcdowell, Teresa; Perumbilly, Sebastian; Titus, Gayatri (Journal of Systemic Therapies, 2009)
In this paper, we contribute to an agenda of developing culturally informed practices, centering specifically on working with Asian Indian and Asian Indian American families. We report the results of a modified Delphi study in which we asked advanced members of the counseling field who are of Asian Indian origin to share their insight relative to family therapy with those who identify as Asian Indian or Asian Indian American in the U.S. Panelists offered a multitude of recommendations, including the importance of: careful assessment that acknowledges within group similarities and differences; attention to extended family ties and intergenerational dynamics; understanding issues of immigration, acculturation, and discrimination; and development of treatment approaches that are congruent with Asian Indian cultural values, beliefs, and practices.
Keywords: dept.mft; peer-reviewed

The Measurement of Outcome Variables in Couple and Family Therapy Research - Sanderson, Jessica; Kosutic, Iva; Garcia, Marisol; Melendez, Tatiana; Donoghue, Jamie; Perumbilly, Sebastian; Franzen, Caroline; Anderson, Stephen (The American Journal of Family Therapy, 2009)
Measurement constitutes a central issue in determining effectiveness of couple and family therapy (CFT). A review of 274 CFT outcome studies published in 25 mental health journals between 1990 and 2005 is presented. Goals of this review were to (1) provide a broad, empirically based overview of CFT outcome research, (2) examine measurement of treatment outcomes, and (3) appraise reporting practices. Findings indicate that a wide range of instruments continue to be used in CFT outcome research, although a foundation for a more integrated and coherent assessment battery has been established. Implications for the field are discussed.
_eprint: https://doi.org/10.1080/01926180802405935
Keywords: dept.mft; peer-reviewed

Theorizing the Emergence of Change in Daily Living: Developing a Contextual Framework for Social Work Practice. - Keenan, Elizabeth King (2008)
Keywords: dept.swk; faculty_collection; sabbatical_report

Early Detection of Schizophrenia: Phenomenological Markers. - Rakfeldt, Jaak (2000)
Keywords: dept.swk; faculty_collection; sabbatical_report

Diversity, Oppression, and Social Functioning: Person-in-Environment Assessment and Intervention - Appleby, George A. (Pearson/Allyn and Bacon, 2007)
Keywords: Social work with minorities; Person-in-environment system; dept.swk; faculty_collection

A Dream and a Plan: A Woman's Path to Leadership in Human Services - Gardella, Lorrie Greenhouse; Haynes, Karen S.; National Association of Social Workers (NASW Press, 2004)
Keywords: Administration; Leadership; Promotions; United States; United States; Career development; United States; Human services; United States; Women executives; United States; Women social workers; Women social workers; dept.swk; faculty_collection

Working-Class Gay and Bisexual Men - Appleby, George A. (Harrington Park Press, 2001)
Keywords: Services for; Services for; Bisexual men; Social work with gays; Gays; dept.swk; faculty_collection

Diversity, Oppression, and Social Functioning: Person-in-Environment Assessment and Intervention - Appleby, George A.; Colon, Edgar; Hamilton, Julia (Allyn and Bacon, 2001)
Keywords: Social work with minorities; Person-in-environment system; dept.swk; faculty_collection

Introduction - Flynn, D.S.; Siegel, E. (Gerontology and Geriatrics Education, 2001)
0 citations (Crossref) [2023-10-31]
Keywords: dept.swk

The supervisor in aging services - Corley, C.S.; Takamura, J.; Siegel, E. (Supervision as Collaboration in the Human Services: Building a Learning Culture, 2004)
Journal Abbreviation: Superv. as Collaboration in the Hum. Services: Building a Learning Culture
Keywords: dept.swk

The impact of terrorism, terror and trauma on children: Implications for treatment - Marvasti, J.A.; Dripchak, V.L. (American Journal of Forensic Psychiatry, 2004)
Keywords: alcohol; antidepressant agent; article; battle injury; behavior therapy; beta adrenergic receptor blocking agent; case report; child; child behavior; cognitive therapy; cultural factor; cyproheptadine; dept.swk; family violence; fear; female; fluoxetine; human; imipramine; immune system; male; nightmare; paroxetine; play therapy; posttraumatic stress disorder; propranolol; psychotrauma; self medication; serotonin uptake inhibitor; sertraline; sexual abuse; street drug; terrorism; tricyclic antidepressant agent; ⛔ No DOI found

Managing school discipline and implications for school social workers: A review of the literature - Cameron, M. (Children and Schools, 2006)
School disciplinary policies and practices are essential features of life in U.S. schools. Conventional approaches to school discipline - including conduct codes and security methods, suspension, corporal punishment, and teachers' methods of managing student behaviors - rely primarily on deterrence, control, and punishment to maintain order. However, approximately 40 years of research, chiefly in education and psychology, has demonstrated that these policies and practices are often associated with and can contribute to increased disorder in schools and behavioral and academic problems among students. Furthermore, school discipline is sometimes administered prejudicially to those students who may be the most vulnerable. School social workers and all social workers working with children and youths can help schools adopt effective and nonpunitive disciplinary approaches. Key professional actions include advocacy for schoolchildren subject to unfair and overly punitive discipline; educating teachers and administrators about the potential harm associated with conventional disciplinary practices; educating school personnel about effective, nonpunitive approaches; and creating a public campaign to generate popular support for the reform of iatrogenic school disciplinary practices. © 2006 National Association of Social Workers.
48 citations (Crossref) [2023-10-31]
Keywords: Children; Discipline; Punishment; School social work; Schools; dept.swk

School discipline and social work practice: Application of research and theory to intervention - Cameron, M.; Sheppard, S.M. (Children and Schools, 2006)
Research has identified a relationship between school disciplinary actions and poor academic and psychosocial functioning of students subjected to them. The ways in which school discipline is a direct contributor to students' academic and psychosocial difficulty needs to be further established empirically. Several theories, based in existing research and theory in sociology of education and educational psychology, have been proposed to explain the school discipline - student dysfunction relationship. They generally suggest three pathways: disciplinary actions may contribute to students' psychological problems; student misbehavior may be encouraged through ineffective and unintentionally paradoxical learning experiences; and disciplinary practices may damage students' relationship with school. School social workers and others working with children who have been disciplined at school can use these research findings and theories as an assessment framework to guide their interventions.The awareness of the iatrogenic potential of school discipline and informed assessment can support a range of evidence-based alternatives to school discipline. © 2006 National Association of Social Workers.
27 citations (Crossref) [2023-10-31]
Keywords: Assessment; Children; Discipline; School social work; Schools; dept.swk

Social work practice with LGBT people within organizations - Appleby, G.A.; Colon, E. (Soc. Work Pract. with Lesbian Gay Bisexual and Transgender People: Second Ed., 2008)
Journal Abbreviation: Soc. Work Pract. with Lesbian Gay Bisexual and Transgender People: Second Ed.
Keywords: dept.swk

A case for developing the emotional capacities of social workers: A commentary on “Promoting self-awareness: Infant observation training as a model” - Bliss, S (Smith College Studies in Social Work, 2005)
tex.unique-id: ISI:000232698200005
Keywords: dept.swk; ⚠️ Invalid DOI

Mass trauma and violence: Helping families and children cope. - Dripchak, VL (Clinical Social Work Journal, 2005)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000233770000011
Keywords: dept.swk

Introduction to the book reviews - Vol. 33 Iss. 1 - Keenan, EK (Clinical Social Work Journal, 2005)
1 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000229030100008
Keywords: dept.swk

Introduction to the book reviews - Vol. 33 Iss. 2 - Keenan, EK (Clinical Social Work Journal, 2005)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000231815900008
Keywords: dept.swk

Introduction to the book reviews - Vol. 33 Iss. 3 - Keenan, EK (Clinical Social Work Journal, 2005)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000232414100008
Keywords: dept.swk

Introduction to the book reviews - Vol. 33 Iss. 4 - Keenan, EK (Clinical Social Work Journal, 2005)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000233770000009
Keywords: dept.swk

Parallel processes in community- based research - Keenan, Elizabeth King (Reflections: Narratives of Professional Helping (Click on Current or Archives; Registration Optional), 2005)
Citation Key Alias: lens.org/149-209-837-126-977
Keywords: dept.swk; peer-reviewed; ⛔ No DOI found

Micro ruptures and repairs in the beginning phase of cross-cultural psychotherapy - Keenan, Elizabeth; Tsang, A.; Bogo, Marion; George, Usha (Clinical Social Work Journal, 2005)
The article discusses misunderstandings and misattunements that occur in the beginning phase of cross-cultural psychotherapy. Sources of micro ruptures are outlined, including client maladaptive patterns, therapist misunderstandings, cross-cultural misunderstandings due to cultural variations, and asymmetrical power relations involving the impact of prior experiences or current therapy practices. Multiple clinical vignettes illustrate the rupture/repair process, drawing on Safran and Muran's (2000) list of direct and indirect techniques., (C)2005 Kluwer Academic Publishers
12 citations (Crossref) [2023-10-31] Place: (C)2005 Kluwer Academic Publishers
Keywords: Beginning phase of psychotherapy; Cross-cultural psychotherapy; Rupture and repair; Therapeutic relationship; beginning phase of psychotherapy; cross-cultural psychotherapy; dept.swk; rupture and repair; therapeutic relationship

Do social workers integrate sociocultural issues in mental health session dialogue?: an exploratory study of cross-cultural practice - Keenan, Elizabeth King; Tsang, A. Ka Tat; Bogo, Marion; George, Usha (Social Work in Mental Health, 2004)
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00196 tex.type: [object Object]
Keywords: dept.swk

From sociocultural categories to socially located relations: Using critical theory in social work practice - Keenan, EK (Families in Society-the Journal of Contemporary Human Services, 2004)
This article applies concepts from critical social theories to shift the profession's discourse from the center-margin relations of generalist-multicultural practice to a model of socially located cross-cultural client-worker relationships. Critical theories examine patterns and meanings enacted within and between people in specific social locations at specific points in history that express particular relations of culture, power, and identity. This framework can help social workers listen, explore, conceptualize, and intervene in a more complex and effective manner. The article summarizes key themes in critical theories, redefines how social workers can use knowledge for practice, and concludes with discussion of a case illustration.
12 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000226071200011
Keywords: dept.swk

Cacophony, polyphony or fugue: Exploring sociocultural concepts with social work students - Keenan, Elizabeth King; Miehls, Dennis; Moffatt, Kenneth; Orwat, John; White, Joyce (Smith College Studies in Social Work, 2004)
This paper documents some dialogue among the authors that emerged as each taught Master of Social Work students a course in sociocultural concepts. The instructors taught this required course from a common syllabus and the discussion reflects the authors' experiences in the delivery of the course material. At the time these dialogues took place, the instructors had recently changed the course format. Rather than teaching sociocultural concepts in isolation (eg. a class on sexism, a class on ageism, etc.), the instructors crafted the course content around central themes. Postmodern theories underscore much of the course content, and are synthesized both in this course and across the curriculum with feminist, psychodynamic, and cross-cultural practice theories. The paper begins by summarizing key post-modern theories that frame the course. Then, the authors respond to formulated questions that address multiple forms of identity development, ambiguity, and competing student ideologies that are manifest in classroom dynamics. Finally, the authors discuss their respective pedagogical and theoretical views and discuss their classroom experiences.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-164-803-188-190 tex.type: [object Object]
Keywords: dept.swk

Culture and psychoanalytic theory - Introduction to the book reviews - Keenan, EK (Clinical Social Work Journal, 2004)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000223461500008
Keywords: dept.swk

Introduction to the book reviews - Vol. 32 Iss. 1 - Keenan, EK (Clinical Social Work Journal, 2004)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000220649800009
Keywords: dept.swk

Introduction to the book reviews - Vol. 32 Iss. 2 - Keenan, EK (Clinical Social Work Journal, 2004)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000221497400008
Keywords: dept.swk

Working models: A tool for synthesizing psychology, culture, and power in everyday experiences and internal representations - Keenan, Elizabeth King (Smith College Studies in Social Work, 2003)
As social beings, we experience ourselves through interactions with others in daily routines that participate in the cultural practices and power relations of broader social structures. Social workers, and social scientists in general, however, have had difficulty conceptualizing and synthesizing this way of being in the world. This paper attempts to respond to that gap by discussing how clinical social workers can use the concept of working models as a tool for listening and understanding in psychotherapy. Utilizing a case example, the paper will discuss three working models, the enactment of power relations, cultural practices, and psychological processes, which provide an integrative framework to inform clinical work.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/018-182-490-831-257 tex.type: [object Object]
Keywords: dept.swk

Whole-school violence prevention program: A university-public school collaboration - Haymes, Elayne; Howe, Esther; Peck, Lynne (Children & Schools, 2003)
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/155-622-226-996-128 tex.type: [object Object]
Keywords: dept.swk

Introduction to the book reviews - Vol. 31 Iss. 2 - Keenan, EK (Clinical Social Work Journal, 2003)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000183231200008
Keywords: dept.swk

Introduction to the book reviews - Vol. 31 Iss. 3 - Keenan, EK (Clinical Social Work Journal, 2003)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000184505200009
Keywords: dept.swk

Introduction to the book reviews - Vol. 31 Iss. 4 - Keenan, EK (Clinical Social Work Journal, 2003)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000186499400008
Keywords: dept.swk

Book Review: object relations theory and self psychology in social work practice. eda g. goldstein. new york: the free press, 2001, 303 pp., 35.00 - Keenan, Elizabeth King (Clinical Social Work Journal, 2002)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/046-691-955-325-014 tex.type: [object Object]
Keywords: book.review; dept.swk

Ethnographic study of gay and bisexual working-class men in the united states - Appleby, George Alan (Journal of Gay and Lesbian Social Services, 2001)
24 citations (Crossref) [2023-10-31] Citation Key Alias: pop00144 tex.type: [object Object]
Keywords: dept.swk

An ethnographic study of six latino gay and bisexual men - Colon, Edgar (Journal of Gay and Lesbian Social Services, 2001)
7 citations (Crossref) [2023-10-31] Citation Key Alias: pop00151 tex.type: [object Object]
Keywords: dept.swk

Distance learning in gerontological education: results and implications of a national survey - Tompkins, Catherine J.; Siegel, Elbert (Gerontology & Geriatrics Education, 2001)
This article reports data collected from a national survey of the Association for Gerontology in Higher Education’s (AGHE) member institutions conducted in 1998. The purpose was to explore current usage of distance learning in gerontological education. The findings suggest that distance learning is being implemented within various programs throughout the country with many others showing an interest. The strengths and limitations of using distance learning in gerontological education are discussed. [Article copies available for a fee from The Haworth Document Delivery Service: 1-800-342-9678. E-mail address: <getinfo@haworthpressinc.com> Website: <http://www.HaworthPress.com>]. © 2001 by The Haworth Press, Inc. All rights reserved.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00279 tex.type: [object Object]
Keywords: dept.swk

Ethnographic study of twenty-six gay and bisexual working-class men in australia and new zealand - Appleby, George Alan (Journal of Gay and Lesbian Social Services, 2001)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-359-479-706-643 tex.type: [object Object]
Keywords: dept.swk

Implications for clinical and policy practice - Appleby, George Alan (Journal of Gay and Lesbian Social Services, 2001)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-475-049-848-910 tex.type: [object Object]
Keywords: dept.swk

Interviewing working-class gay men over the internet - Appleby, George Alan (Journal of Gay and Lesbian Social Services, 2001)
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/051-662-724-899-983 tex.type: [object Object]
Keywords: dept.swk

Practice and theoretical knowledge-based theory for clinical and policy practice - Appleby, George Alan (Journal of Gay and Lesbian Social Services, 2001)
SUMMARY: Practice with working-class gay and bisexual men draws upon an ecological framework with a strengths perspective, which emphasizes the roles of culture, values, social class, social identity development, social categorization, social comparison, oppression and power, diversity, and stigma. This practice is based upon a process of developing an assessment and selecting a range of human service interventions. Ethnographic studies were conducted throughout the United States and Canada using a broad-based sample of working-class men to enhance our understanding of their needs and effective ways of helping. © 2001, Taylor & Francis Group, LLC.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/170-732-264-616-422 tex.type: [object Object]
Keywords: And intervention; Assessment; Culture; Diversity; Ecology; Individual and group identity; Oppression and power; Social class; Stigma; Strengths; Values; dept.swk

"It was just realizing... that life isn't one big horror": A qualitative study of supported socialization - Davidson, L.; Haglund, K.E.; Stayner, D.A.; Rakfeldt, J.; Chinman, M.J.; Tebes, J.K. (Psychiatric Rehabilitation Journal, 2001)
This report describes the qualitative component of a large-scale study of supported socialization. Paralleling the recent advances made through supported housing, supported employment, and supported education, this approach seeks to increase the involvement of individuals with psychiatric disabilities in naturally occurring social and recreational activities in community settings of their choice. After a review of social relationships and psychiatric disability, we describe the Partnership Project and present findings from a series of qualitative interviews conducted with a subsample of participants. We then discuss the implications of these findings for the community integration of individuals with psychiatric disabilities.
90 citations (Crossref) [2023-10-31]
Keywords: adult; article; clinical article; dept.swk; education; employment; female; health program; housing; human; human relation; integration; life; male; mental disease; questionnaire; recreation; socialization; support group; therapeutic community

A new perspective: the common factors model as a foundation for social work practice education - Cameron, Mark; Keenan, Elizabeth King (Journal of Teaching in Social Work, 2009)
Foundation social work practice education is critical to the preparation of BSW practitioners for professional practice and the establishment of a theoretical and skill base upon which graduate students may build competencies in the advanced curriculum. Issues in the foundation practice curriculum may hinder this development. The common factors model holds promise as an organizing framework for foundation social work practice education. This model may help to resolve some key issues in social work and social work education, and may provide a useful, coherent, and empirical base for the foundation practice curriculum. © Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/061-482-221-756-184 tex.type: [object Object]
Keywords: Common factors; Direct practice; Foundation curriculum; Practice education; dept.swk; peer-reviewed

Teaching organization theory and practice: an experiential and reflective approach - Cameron, Mark; Turkiewicz, Rita M; Holdaway, Britt A; Bill, Jacqueline S; Goodman, Jessica; Bonner, Aisha; Daly, Stacey; Cohen, Michael D; Lorenz, Cassandra; Wilson, Paul R; Rusk, James (Journal of Teaching in Social Work, 2009)
The organization is often the overlooked level in social work's ecological perspective. However, organizational realities exert a profound influence on human development and well-being as well as the nature and quality of social work practice. This article describes a model of teaching organization theory and practice which requires master's social work students to assess their school of social work as well as their field placement agencies. Teaching organization theory and practice experientially may help students understand how organizations influence practice and empower them to see organization practice as a legitimate and important aspect of their work.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/022-043-403-165-052 tex.type: [object Object]
Keywords: Field education; Macro; Organization; Practice; Teaching; dept.swk; peer-reviewed

Book Review: Run: A novel - Rakfeldt, Jaak (Psychiatric Services, 2008)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000261187300031
Keywords: book.review; dept.swk

Refusing the right to refuse: Coerced treatment of mentally disordered persons - Rakfeldt, Jaak (Psychiatric Services, 2008)
1 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000253444500022
Keywords: dept.swk

Crisis intervention handbook: Assessment, treatment, and research - Bliss, Susan (Smith College Studies in Social Work, 2008)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000257342900004
Keywords: dept.swk

Third Space Activities and Change Processes: An Exploration of Ideas from Social and Psychodynamic Theories. - Keenan, Elizabeth; Miehls, Dennis (Clinical Social Work Journal, 2008)
Discussions pertaining to culture, power and/or identity frequently create tensions that are enacted by dyads and groups within schools, workplaces and communities. Although tensions can easily escalate into conflict or violence, we have observed that these tensions can serve as prompts that promote a change process. When individual perspectives are challenged, some participants are able to dissemble their views and consider other perspectives from which new understandings and views emerge. At times, when groups seem to be on the threshold of overt conflict, some participants engage in processes that examine the tension, explore new possibilities, and alter the view of one's subjectivity. We suggest that these activities occur as momentary states in psychological spaces conceptualized as third spaces (Bhabha, The location of culture. London: Routledge, 1994). In this paper, we use concepts from psychodynamic and social theories to describe the conditions that coalesce to form states of mind (nepantla) (Anzaldua, Borderlands/La Frontera: The new mestiza. San Francisco: Aunt Lute Books, 1999; Interviews Entrevistas. New York: Routledge, 2000) and the ability to engage in new relational possibilities (third space activities) with dyads and groups, outside of psychotherapy. The conditions include: critical consciousness, regulation, recognition, and responsibility. We then describe how such momentary experiences can subsequently result in an examination of one's subjectivity, particularly as it pertains to issues regarding culture, power, and identity. Throughout the paper we provide four examples from various settings to illustrate these concepts and processes. Given the increasing racial/ethnic diversity of clients and clinical social workers in North America, this concept of third spaces holds particular relevance for contemporary clinical social work practice., (C)2008 Kluwer Academic Publishers
10 citations (Crossref) [2023-10-31] Place: (C)2008 Kluwer Academic Publishers
Keywords: Change processes; Psychodynamic theory; Social theory; Third space activities; dept.swk

Reflections from a student of mothering - Schneider, Dana (Smith College Studies in Social Work, 2008)
This reflective article provides a window into one clinical social worker's experience of returning to school after becoming a mother. The convergence of two separate lives, those of mother and student, is explored through a psychodynamically-informed perspective. Challenges of integrating theories on mothering from an experience-near position are discussed.
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000260696300006
Keywords: dept.swk

Posttraumatic play: Towards acceptance and resolution - Dripchak, Valerie L. (Clinical Social Work Journal, 2007)
Many children who experience trauma demonstrate it through posttraumatic play (PTP). This type of play is seen by professionals as a repetitive reenactment of the traumatic event within the child's play. Reliving the event in this way may serve to retraumatize the child and lead to other psychiatric or behavioral problems. This article examines the issues surrounding childhood trauma and PTP. It uses a case study to illustrate the phases of a play therapy approach that incorporates Ericksonian principles, in order for the child to achieve resolution and acceptance. The countertransference issues that a clinician may encounter also are discussed.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/049-629-250-370-634 tex.unique-id: [object Object]
Keywords: Play therapy; Posttraumatic play; Retraumatize; Trauma in children; dept.swk

Lesbian mothers with planned families: A comparative study of internalized homophobia and social support - DeMino, Kathleen A.; Appleby, George; Fisk, Deborah (American Journal of Orthopsychiatry, 2007)
This study compared the perception of social support and the degree of internalized homophobia for two demographically similar groups: lesbians with planned families and lesbians who did not have children. Results found that lesbians with planned families perceived significantly less social support from friends overall, from gay men and lesbian friends specifically, and more support from their families-of-origin than lesbians who did not have children. Lesbians with planned families also reported significantly higher internalized homophobia specific to disclosure of sexual identification. The authors suggest that selective disclosure may be an adaptive response rather than a true measure of internalized homophobia.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/091-948-881-682-440 tex.unique-id: [object Object]
Keywords: Adult; Attitude; Child; Family Planning Services; Female; Homosexuality; Female; Humans; Internalized homophobia; Lesbian mothers; Maternal Behavior; Mothers; Percerption of social support; Planned families; Questionnaires; Self Concept; Social Support; adult; article; controlled study; demography; dept.swk; family; female; gender identity; homophobia; human; lesbian; male homosexual; social support

Diagnosing conduct problems of children and adolescents in residential treatment - Cameron, Mark; Guterman, Neil B (Child Care Quarterly, 2007)
This naturalistic study of diagnostic practice in residential treatment agencies for children investigated the use of the DSM-IVconduct disorder diagnosis and its association with residents' externalizing behaviors. The conduct disorder (CD) diagnosis was a poor predictor of participants' externalizing behaviors during their first few months in residence. Additionally, the assignment of the diagnosis was associated with the gender and race of study participants. Decisions of admissions personnel and practitioners in residential treatment facilities regarding their externalizing clients may not be well-served by use of DSM diagnoses. Assessments of caregivers may prove a useful adjunct to DSM diagnoses. © 2007 Springer Science+Business Media, LLC.
22 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-610-397-897-543 tex.type: [object Object]
Keywords: Adolescents; Children; Conduct disorder; DSM-IV validity; Diagnosis; Residential treatment; dept.swk

Patterns of interaction: Conceptualizing the crossroads between social structures, interpersonal actions, and psychological well-being - Keenan, Elizabeth King (Smith College Studies in Social Work, 2007)
Patterns of interaction theory directs social workers' attention to the relations between structures (psychological and social), and actions: the crossroads of continuity and change. Because it describes sequences of action by key participants that generate specific options at various points in a sequence, it serves as both theory and method for understanding and intervening with human beings and social structures. The use of patterns of interaction as an overarching construct illuminates the reciprocal relationships between social structures, interpersonal actions, and psychological well-being. This paper outlines a preliminary conceptualization of patterns of interaction theory and the methodology that grows out of it. The social service programs of Temporary Assistance to Needy Families (TANF) and a community-based case management welfare-to-work program illustrate how an ethical lens applied to patterns of interaction can help social workers intervene within complex relations to facilitate client growth. Patterns of interaction theory is a potentially effective way of describing and analyzing the therapeutic effects of a range of different social service programs.
tex.unique-id: ISI:000245064200005
Keywords: dept.swk; ⚠️ Invalid DOI

The good life - Rakfeldt, Jaak (Psychiatric Services, 2006)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000242534500051
Keywords: dept.swk

Assertive outreach: An effective strategy for engaging homeless persons with substance use disorders into treatment - Fisk, Deborah; Rakfeldt, Jaak; McCormack, Erin (American Journal of Drug and Alcohol Abuse, 2006)
The purpose of this study was to examine substance abuse treatment referrals that were made by outreach workers in a homeless outreach project. Ten outreach workers completed questionnaires on each of their clients who they had referred to a substance abuse treatment program over the previous year. Additional data was collected on the client's motivation level at the point the referral was made, which agencies the client was referred to, and if the client was rejected from any of the treatment programs. Bivariate correlation analyses were used to examine relationships between the variables. Of 73 project clients who were referred to substance abuse treatment in a one-year period of time, 41% successfully entered treatment. As might be expected, there was a statistically significant relationship between clients' motivation level and completed referral, and between referrals made and program acceptance. This study provides evidence that assertive outreach is effective in engaging and linking homeless persons with substance use disorders to substance abuse treatment services.
26 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/063-067-831-831-545 tex.unique-id: [object Object]
Keywords: Adolescent; Adult; Assertive outreach; Community-Institutional Relations; Female; Homeless Persons; Homeless populations; Humans; Male; Middle Aged; Substance abuse; Substance-Related Disorders; Treatment Outcome; adult; article; assertiveness; correlation analysis; dept.swk; drug dependence treatment; female; homelessness; human; major clinical study; male; mental health service; motivation; patient referral; social work; social worker; statistical significance; substance abuse

My father the spy: An investigative memoir - Rakfeldt, J (Psychiatric Services, 2006)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000237301500049
Keywords: dept.swk

Weight bias: Nature, consequences, and remedies. - Howe, Esther (Clinical Social Work Journal, 2006)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000241716500017
Keywords: dept.swk

Introduction to the book reviews - Vol. 34 Iss. 1 - Keenan, EK (Clinical Social Work Journal, 2006)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000235724700008
Keywords: dept.swk

Introduction to the book reviews - Vol. 34 Iss. 2 - Keenan, Elizabeth King (Clinical Social Work Journal, 2006)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00350 tex.type: [object Object]
Keywords: dept.swk

Introduction to the book reviews - Vol. 34 Iss. 3 - Keenan, Elizabeth King (Clinical Social Work Journal, 2006)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000238828500012
Keywords: dept.swk

Introduction to the book reviews - Vol. 34 Iss. 4 - Keenan, Elizabeth King (Clinical Social Work Journal, 2006)
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000241716500012
Keywords: dept.swk